Optimization of the Use of the Barber-Johnson Chart on the Efficiency of Bed Management in the Kabupaten Kediri Hospital - Ratna Wardani; Zainal Arifin (Journal of Community Engagement in Health, 2024)
The level of efficiency in bed use in hospitals using 4 (four) parameters, namely Bed Occupancy Ratio (BOR), Average Length of Stay (AvLOS), Internal Turnover (TOI), and Bed Turnover (BTO). Hospitals that do not utilize the Barber-Johnson Chart will have difficulty describing inpatient performance, comparing rooms, and even being unable to control reporting errors. Hospitals use Barber Johnson charts to conduct evaluations to improve efficiency in hospitals. As one of the determining variables of the four parameters, bed capacity cannot be easily reduced or added due to regulations. Adjust the number of beds according to the class needed by the patient; for example, if the patients at the Hospital of Kabupaten Kediri are mostly National Health Insurance class I and class III participants, then the ratio of the number of beds in class I and class III is more than class II, and so on. The BOR value has increased from year to year, along with the number of patients, treatment days, and length of treatment. The AvLOS and TOI scores have met the ideal figures, so the quality of health services at the Hospital of Kabupaten Kediri is good.